2018
DOI: 10.15740/has/ijas/14.1/229-234
|View full text |Cite
|
Sign up to set email alerts
|

Rooting and shooting behaviour of red and white pulped varieties of dragon fruit (Hylocereus undatus) in relation to indole butyric acid concentrations

Abstract: The investigation was carried out to study the effect of IBA at different concentrations (2000ppm, 4000ppm, 6000ppm) on cuttings of dragon fruit cultivars viz., red pulped variety and white pulped variety to elicit their rooting and shooting parameters. The cuttings of the red pulped variety performed better than the white pulped variety. Indole butyric acid (IBA) had significant effect on rooting and shooting performance of both the varieties over control. IBA @ 6000 ppm recorded minimum number of days for sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…The increases in dry weight of roots have directly influenced the length of roots, and the number of roots. The present findings are in conformity with the results in dragon fruit (Rahad et al 2016, Chahal 2020, Dhruve et al 2018, pomegranate (Deshmukh et al 2019), and mahogany cuttings (Sondarva et al 2017).…”
Section: Also Increase In Root Volumesupporting
confidence: 93%
“…The increases in dry weight of roots have directly influenced the length of roots, and the number of roots. The present findings are in conformity with the results in dragon fruit (Rahad et al 2016, Chahal 2020, Dhruve et al 2018, pomegranate (Deshmukh et al 2019), and mahogany cuttings (Sondarva et al 2017).…”
Section: Also Increase In Root Volumesupporting
confidence: 93%
“…On the other hand, the number of new shoots differed among genotypes (P<0.05). A previous study reported that dragon fruit with red-pulped fruits generated a higher number of new shoots than the white-pulped genotypes under no auxin treatment [10]. In our study, the lower number of new shoots for the 'White' genotypes may be related to ant infestation.…”
Section: Effect Of Genotypesupporting
confidence: 43%
“…However, effects observed on root performance of H. undatus were a result of the application of high concentrations of auxins. Previous studies found that the application of IBAwas effective at a concentration ranging from 6000 ppm to 7000 ppm [9][10]. These concentrations are surprising given the knowledge that auxins are effective even at very low concentrations and auxins applied at high dose may actually be damaging [11].…”
Section: Commercial Growth Regulator For Dragon Fruit Cuttings In Gre...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that the greater number of shoots observed in cuttings treated with the biostimulant SprintAlga TS®, especially for Brewer's Gold, may be related to the presence of hormones that have an effect on plant growth such as cytokinins (CALVO et al 2014, MICHALAK et al 2016. It was observed in other studies that cuttings treated with cytokinins such as Benzyladenine present a greater number of shoots (ELOBEIDY 2006, DHRUVE et al 2018, SIDDIQUA et al 2018.…”
Section: Number Of Shoots and Shoot Lengthmentioning
confidence: 98%